The Effect of Combustion Chamber Volume and Engine Rotation on Temperature and Compression Pressure of Single Cylinder Diesel Engine - Prasetyo, Sigit; Irawan, Bambang (Evrimata: Journal of Mechanical Engineering, 2024)
The effect of combustion chamber volume and engine rotation on the temperature and compression pressure of this single-cylinder diesel engine aims to convert the use of diesel fuel in diesel engines into gasoline fuel by utilizing high compression without using the help of spark plugs during ignition. The main focus of the study is to understand the effect of variations in combustion chamber volume and engine rotation on temperature and compression pressure in order to find optimal operating conditions. The General 170fd single-cylinder diesel engine was used as the object of research. The testing tools used include the TC-08 Thermocouple sensor module, the thermocouple sensor, and the pressure gauge to measure the temperature and compression pressure. The research was carried out using various gasket thicknesses, namely 0.6mm, 0.8mm, 1.4mm, 1.6mm, and 1.8mm to vary the volume of the combustion chamber. The data collected was analyzed to determine the relationship between changes in the volume of the combustion chamber and engine rotation to the temperature and compression pressure. The results of the study are expected to provide insight into the ideal conditions for gasoline ignition in diesel engines without the use of spark plugs, as well as contribute to efforts to optimize the use of alternative fuels. The results of the experiment showed that variations in the volume of the combustion chamber and engine rotation had a significant impact on the temperature and compression pressure. The determination of the appropriate temperature and compression pressure is expected to improve the efficiency and performance of diesel engines when using gasoline fuel, thereby reducing operational costs and increasing the flexibility of engine use in various applications. This research makes an important contribution to the understanding of diesel engine modifications for gasoline fuel use, which can be applied without testing exhaust emissions, with a focus on ideal temperature and compression pressure.